Application of artificial intelligence by university students: Chinese case - Liudmyla Holubnycha; Tetiana Besarab; Tetiana Fomenko; Yaroslav Сhernonkov; Iryna Hontarenko; Tetyana Koshechkina (Institute of Advanced Engineering and Science, 2025)
The problem of artificial intelligence (AI) use is crucial for understanding how AI creates new opportunities in education. It is proposed an approach designed to elicit precise responses regarding the students’ practical application of AI. The purpose of the research is to investigate Chinese students’ attitude to using AI that affect learning activities. The research design employed the methods of questionnaire and calculating. The questionnaire consisted of questions about using AI for different tasks, assignments, activities. The study was conducted in 2024. The research participants were 187 bachelor students from Shangqiu Normal University in China. A sampling technique was used as the students were selected based on their willingness to participate in the survey. The key findings are: over half of Chinese students use AI for presentations, essays, and projects, while a notable minority do not. More students use AI for professors’ tasks. The highest AI use is for homework. Fewer than half rely on AI for exam preparation, favoring traditional study methods. The conclusion is students in China tend to rely more on AI for routine or repetitive tasks. It is recommended to focus on developing AI literacy programs that guide students in the effective use of AI.